Prevalence of metabolic syndrome in dialysis and transplant patients - Alshelleh S (Dove Medical Press, 2019)
Sameeha AlShelleh,1 Izzat AlAwwa,1 Ashraf Oweis,2 Saif Aldeen AlRyalat,1 Mohammad Al-Essa,1 Iyad Saeed,1 Hussein H Alhawari,1 Karem H Alzoubi31Department of Internal Medicine, The University of Jordan, Amman 11942, Jordan; 2Department of Internal Medicine, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, JordanBackground: Several epidemiological studies have assessed various components of Metabolic Syndrome (MS) in different populations, but only a few compared the prevalence of metabolic syndrome in dialysis and transplant patients.Aim: The aim of this study is to compare the prevalence of MS in dialysis and transplant patients. Two groups of patients were included; hemodialysis patients and patients with transplanted kidneys.Methods: Demographic and clinical history, and lab data were collected. A total of 108 patients were included in this study with a mean age of 52.3 (±16.29) years. Study groups included 61 (56.5%) dialysis patients, and 47 (43.5%) patients with transplanted kidneys.Results: Upon comparing the prevalence of metabolic syndrome between the two study groups, transplant patients had significantly lower prevalence of metabolic syndrome (34%) compared to that of metabolic syndrome in patients on dialysis (55.7%; P=0.016).Conclusion: As metabolic syndrome plays an important role in the pathology of elderly patients, especially those with transplanted kidneys, such findings indicate the need for close monitoring of kidney transplant patients for the manifestations of metabolic syndrome.Keywords: metabolic syndrome, renal transplant, chronic kidney disease, elderly